Plackett–burman design as a tool for screening and process optimization of rivastigmine-loaded lipid nanocarriers - Anand, Anubhav; Singh, Gyanendra; Saraf, Shubhini A (Innovare Academics Sciences Pvt. Ltd, 2019)
Objective: Plackett–Burman experimental design is used to identify the most important factors early in the experimentation phase when complete knowledge about the system is usually unavailable. The objective of this study was to screen out the most important factors affecting the size and entrapment efficiency of rivastigmine hydrogen tartrate (RHT) nanostructured lipid carriers (NLCs). Methods: The RHT-loaded NLC was prepared by the modified solvent emulsification-diffusion method. The independent variables selected for Plackett–Burman design were drug: lipid ratio, solid lipid/liquid lipid (S/L) ratio, concentration Ryoto sugar ester (%w/v), the concentration of poloxamer 188 (%w/v), sonication time (min), sonication amplitude, and stirring time (h). Results: The R2 value for the particle size equation was 86.16%. p value was (<0.05) 0.048 in case of sonication time. In case of entrapment efficiency, the R2 value was 87.12%. The p value (p<0.05) for S/L ratio and the Ryoto sugar (% w/v) was 0.028 and 0.042, respectively. Conclusion: It can be concluded that sonication time has a significant effect on particle size, whereas S/L ratio and Ryoto sugar ester concentration have a significant effect on entrapment efficiency.
Keywords: Burman; Nanostructured lipid carrier; Plackett; Rivastigmine